Implementation of Educational Game System Using MDLC with Adobe Animate Application - Kiki Setiawan; Dede Sarikah (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Digital gaming has transformed educational practices across Indonesia, creating new pathways for curriculum delivery through interactive entertainment. Educational games now serve as effective learning tools that capture student attention while building essential skills. The research develops and evaluates a multi-level educational puzzle game using Adobe Animate 2022, targeting cognitive skill enhancement and problem-solving abilities across different age groups. Development followed the Multimedia Development Life Cycle (MDLC) approach through six phases: conceptualization, design planning, resource gathering, system building, testing procedures, and final deployment. The puzzle application includes three difficulty levels with varying complexity parameters. Adobe Animate 2022 handled vector graphics creation, interactive programming, and multi-platform publishing. User evaluation involved testing across target demographics to assess usability and learning effectiveness. The finished application successfully demonstrates structured game development using MDLC principles. Testing showed positive user responses with balanced difficulty progression and completion rates that indicate effective entertainment-education integration. The development process provided organized workflows that supported quality control and user satisfaction goals. Adobe Animate 2022 proved capable for educational game creation, enabling smooth asset management and publishing operations. The study establishes a reproducible model for future educational gaming projects while validating game-based learning methods in Indonesian educational settings. Findings suggest that systematic development approaches produce superior educational outcomes compared to informal development practices.